Implementation of Career Development Prograams For Cchildren With Special Needs - Premeilani Premeilani; Suharyanto H. Soro (At Turots: Jurnal Pendidikan Islam, 2025)
Career development represents a critical paradigm in conceptualizing the future trajectories of children with special needs. Consequently, these individuals require targeted, equitable, and specialized educational services to actualize their latent potential. Career development programs serve as a concrete pedagogical manifestation designed to equip students with pragmatic abilities, vocational competencies, and psychosocial readiness. This research aims to describe, analyze, and discover the specific models of career development program implementation for children with special needs at SLB BC YPLAB Cibaduyut and SLB BC YPLAB Banjaran. Anchored in a qualitative constructivist paradigm utilizing a case study approach, the research involved vocational educators, Special Job Exchange (Bursa Kerja Khusus/BKK) coordinators, and students with hearing impairments as primary respondents. Data were systematically gathered through participant observation, in-depth interviews, and documentation matrices. The findings reveal that the career program is actualized through four main dimensions: (1) The provision of structured services encompassing orientation, vocational information, and strategic placement; (2) The deployment of adaptive pedagogical methods including direct demonstration, step-by-step instruction, project-based assignments, and continuous training; (3) The management of complex cognitive and communicative barriers through individualized mentoring; and (4) The facilitation of real-world exposure through internships and parental collaboration. Ultimately, the successful implementation of career programs for children with special needs necessitates a holistic synthesis of environmental conditioning, familial support systems, specialized learning experiences, and adaptive coping mechanisms for vocational tasks